Implementation of the strategy by using BSC: a case study in the brazilian public sector - Muscat, Antonio Rafael Namur; de Biazzi, Monica Rottmann; Miguel, Paulo Augusto Cauchick (Revista Gestão da Produção Operações e Sistemas, 2007)
Nowadays, there are many studies on organizational performance, mainly associated with the private sector. Inthe last decades, however, the public sector has also been under pressure to improve its performance and showmore transparency and assessment of results. In this context, some public institutions have sought after managementpractices from the private sector, among them the Balanced Scorecard (BSC). However, the academicliterature on the public sector is relatively scarce, especially in the Brazilian context. In this sense, the objectiveof this paper consists of describing a case study of formulation and implementation of strategy in a Brazilianeducational public institution, by using the methodology of Balanced Scorecard (BSC). The present paper, thestrategic objectives and the measurement suggested are analyzed, evaluating the learning and growth perspectivein more details. The results indicated differences with regard to the traditional BSC application to theprivate sector, in addition to difficulties regarding involvement of the employees, strategy deployment and themeasurement of the suggested performance indicators.Keywords: Balanced Scorecard (BSC); performance measures; public sector.